Women and men in leadership positions in the European Union, 2013 A review of the situation and recent progress - European Commission. Directorate-General for Justice (Λουξεμβούργο : Υπηρεσία Επισήμων Εκδόσεων των Ευρωπαϊκών Κοινοτήτων, 2013)
Equality between women and men is enshrined in the EU Treaties and the EU Charter of Fundamental Rights as a fundamental principle of the European Union (EU). Ensuring gender equality is one of the EU's main objectives and tasks1. It is also a necessary condition for the achievement of the objectives of the Europe 2020 strategy - the EU's growth strategy, which leans on knowledge, competences and innovation. Despite significant progress during the last decades thanks to regulatory pressure, gender inequalities persist in leadership positions and the pace of change is slow in many Member States. In response, the European Commission has reaffirmed its commitment to work to improve the situation by making gender equality in decision-making one of the five priority areas in both the Women's Charter2 and the Strategy for Equality between Women and Men (2010-2015).
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Equality between men and women; Equal treatment; Sexual discrimination; Electronic books